ปัจจัยทางเศรษฐกิจที่มีความสัมพันธ์ต่ออัตราแลกเปลี่ยนระหว่างค่าเงินบาทต่อค่าเงิน - วงษ์ชุ่ม, ธีรวัชร์; พงศ์สุพัฒน์, อภิชาติ (Journal of Buddhist Education and Research (JBER), 2024)
The purpose of this study was to study the economic factors related to the exchange rate between the baht and the yen. The secondary data was collected from January 1, 2017 to December 31, 2021 for 60 months. There were six types of independent variables used in the study such as Balance of Trade (BOT), Consumer Price Index (CPI), Export Price Index (EPI), International Reserve (IR), Exports to Japan : XJP (XJP), and Real Effective Exchange Rate (REER) The results showed that the Consumer Price Index (CPI) and International Reserve (IR) showed a statistically significant positive correlation with the baht-yen exchange rate at 0.05; but the Export Price Index (EPI) and the Real Exchange Rate Index (REER) had a statistically significant negative correlation with the exchange rate between the baht and the yen at 0.05 level, and an equation showing the relationship between the variables is as follows; YEN = 68.855 + 0.287CPI - 0.581EPI + 6.802IR - 0.146REER An R-Squared value of 0.774, indicating that the independent variable used in the equation can be used to describe the dependent variable at 77.40%. But the Balance of Trade (BOT) and Exports to Japan (XJP) are not related to the exchange rate. Therefore, these variables cannot be imported into the equation.